Job stress, quality of work life, job satisfaction and turnover intention among executive level employees of Intel Technology Sdn. Bhd. - Moehanah, Isuarudu (2015)
Employee turnover has always been a matter of concern for organizations. A large degree of employee turnover is highly detrimental to both the organization as well as the employees. The main objective of this study is to explore the factors that influence turnover intention among the executive level employees who are working in Intel Technology Sdn. Bhd. as well as to identify the most significant factor influencing turnover intention. Three independent variables namely job stress, quality of work life, and job satisfaction were examined to determine their relationship with dependent variable, which is turnover intention. A cross-sectional study was chosen for this study. A total of 155 respondents were involved in this study. Data were gathered through questionnaires and was being analysed using Statistical Package for Social Science (SPSS) version 19.0. This study applied descriptive statistics, reliability analysis and inferential analysis to examine the relationship among the variables. The multiple regression analysis of job stress shows that there is a significant and positive relationship on turnover intention. However, there is an insignificant and negative relationship between quality of work life and turnover intention. Besides that, job satisfaction has a significant and negative relationship on turnover intention. Findings of this study also suggested that job satisfaction is the most significant factor that influences turnover intention among executive level employees who worked at Intel Technology Sdn. Bhd. The implication of this study is that organization should take appropriate action during human resource planning as the determinants in increasing employee’s satisfaction and reduce turnover intention. Future research should be including other factors like organizational politics and downsizing that might influence the turnover intention